Effect of short-term, high-dose methylprednisolone on oxidative stress in children with acute immune thrombocytopenia - KOÇ, AHMET (KOREAN SOC HEMATOLOGY, 2016)
Background Immune thrombocytopenia (ITP) is the most common cause of acquired childhood thrombocytopenia and is characterized by increased immune-mediated destruction of circulating thrombocytes. Oxidative damage may be involved in ITP pathogenesis; paraoxonase (PON) and arylesterase (ARE) enzymes are closely associated with the cellular antioxidant system. We investigated the effect of short-term high-dose methylprednisolone (HDMP) treatment on the total oxidant status (TOS), total antioxidant capacity (TAC), oxidative stress index (OSI), and PON and ARE enzymatic activity in children with acute ITP. Methods Thirty children with acute ITP constituted the study group and 30 healthy children constituted the control group. Children with acute ITP were treated with HDMP: 30 mg/kg for 3 days, then 20 mg/kg for 4 days. The TOS, TAC, OSI, PON, and ARE levels were determined before and after 7 days of HDMP treatment. Results The TAC level (P<0.001), and PON (P<0.001) and ARE (P=0.001) activities were lower and the TOS (P=0.003) and OSI (P<0.001) levels were higher in children with acute ITP than those in healthy children in the control group. We also observed statistically significant increases in the TAC (P<0.01), PON (P<0.001) and ARE levels (P=0.001) and decreases in the TOS (P<0.05) and OSI levels (P<0.05) with 7 days of HDMP treatment compared to their values before treatment. Conclusion Our study demonstrated increased oxidative stress (OSI and TOC) and decreased antioxidant capacity (TAC), PON, and ARE in ITP patients and that steroid treatment could be effective in reducing the oxidative stress.
Keywords: ITP; Paraoxonase; Arylesterase; Child; Methylprednisolone; AUTOMATED-METHOD; PARAOXONASE; PURPURA; HDL